Implementation of FFT in Industrial Induction Motor Monitoring via Mobile Phone - Afzeri; Kurnia, Deni; Hakim, Muhammad Nur; Nurmala , Indriani Siti (Journal of Applied Science and Advanced Engineering, 2023)
Competition in the industrial world requires companies to always improve efficiency in the production process. The use of communication technology in the monitoring process is one way to reduce effort in monitoring equipment. This study aims to create a mobile phone-based online control and monitoring system for induction motor parameters in the industry without interfering with the motor's electrical network. The monitoring system is carried out by monitoring the vibration and temperature of the induction motor using the GY-521 MPU-6050 sensor connected to the NodeMCU ESP8266 as the control device. For the data computation process to obtain rotational parameters, the Fast Fourier Transform (FFT) function is applied to transform the vibration data from the accelerometer into the frequency domain. In the data collection process, 250 data samples were captured in 1 second which were formed from vibrations of the X, Y and Z direction motors. Manual ON/OFF control of the electric motor and automatic OFF was carried out when a spike in the vibration frequency of the motor was detected. The test was carried out with four variations of rotation conditions. The test results show that the rpm speed of the motor can be obtained based on the difference in the frequency of motor vibration. This data is then sent online to observer technician via the Telegram application installed on the mobile phone device. The system performance as a whole shows quite good performance both in terms of equipment placement, data processing and delivery.